Portrayal of the Matuas in the Christian Missionary Writings (Journal of the Asiatic Society of Bangladesh, Humanities, 2023)
The paper exposes the socio-economic condition of the early 20th-century Matua community of Bangladesh. It unfolds how the Matuas strived for elevation to the mainstream of national life. They desired for upliftment by securing their rightful and logical position in the broader arena dismantling untouchability and social exclusion imposed on them. They took education as the most suitable medium to make them worthy for every sphere of life. It tells the Australian Baptist missionaries’ outlook on the Matuas and their remarks on the Matuas’ uplifting activities as well as the Matuas’ gradually changing views on life and society. It reflects why the missionaries came to Orakandi. Every single issue of the community has been presented on the basis of the experiences of four missionaries who worked among the Matuas and/or collected a vast knowledge on this once despised backward class of people. Among the four missionaries, three are from the 20th century, and the rest one is from the 21st century and their four relevant books have been selected for this study.Journal of the Asiatic Society of Bangladesh (Hum.), Vol. 68(2), 2023, pp. 241-261